2018
DOI: 10.1111/jpn.12873
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary calcium iodate on productive performance, egg quality and iodine accumulation in eggs of laying hens

Abstract: The aim of this study was to examine the effects of various levels of supplemental calcium iodate (CI) on productive performance, egg quality, blood indices and iodine (I) accumulation in the eggs in commercial laying hens. A total of 240 White Leghorn layers (Hy-line W36) were divided through a completely randomized design into six treatments with five replicates and eight hens per each at 32 weeks of age. This experiment lasted for 12 weeks. Concentrations of I in the mash diets were 0.74, 3.13, 5.57, 8.11, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
2
6
1
Order By: Relevance
“…Besides, with increasing age, there tended to be an increase in the percentage of yolk weight and a decrease in the percentage of albumen weight, which was not altered by dietary iodine. In agreement with our results, Christensen and Ort (1990), Bakhshalinejad et al (2018), and Damaziak et al (2018) reported that dietary inorganic iodine (2.1-12.9 mg/kg as CIOD or KI) had no significant effects on egg yolk and albumen percentages, yolk colour, or Haugh unit. However, Yalçin et al 2004found a linear decrease in albumen index and Haugh unit when the level of dietary iodine increased to 24 mg/kg by using CIOD as the additive, and Lichovnikova et al (2003) reported that even a level of 6.1 mg/kg of iodine could have deleterious effect on Haugh unit in long-term period of treatment (30 wk).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Besides, with increasing age, there tended to be an increase in the percentage of yolk weight and a decrease in the percentage of albumen weight, which was not altered by dietary iodine. In agreement with our results, Christensen and Ort (1990), Bakhshalinejad et al (2018), and Damaziak et al (2018) reported that dietary inorganic iodine (2.1-12.9 mg/kg as CIOD or KI) had no significant effects on egg yolk and albumen percentages, yolk colour, or Haugh unit. However, Yalçin et al 2004found a linear decrease in albumen index and Haugh unit when the level of dietary iodine increased to 24 mg/kg by using CIOD as the additive, and Lichovnikova et al (2003) reported that even a level of 6.1 mg/kg of iodine could have deleterious effect on Haugh unit in long-term period of treatment (30 wk).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are supported by those of Saki et al (2012), who found that eggshell weight and thickness did not respond to dietary inorganic iodine (as CIOD) in a range of 0.8-5.6 mg/kg of diet. However, using the same source of supplement, Bakhshalinejad et al (2018) reported that a level of 10.7 mg/kg of dietary iodine resulted in a reduction of eggshell strength that was independent of weight and thickness of the eggshell. Therefore, the detrimental effect of the EDDI 8 diet on the incidence of abnormal eggs and eggshell strength seems likely to result from a higher level of bioavailable iodine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fathi et al showed that a diet supplemented with probiotics has a beneficial effects on eggshell quality and resistance to breaking. Bakhshalinejad et al found that calcium iodate supplementation increased the accumulation of iodine in eggs and enhanced eggshell strength. Medium chain fatty acid (MCFA) supplementation of feed has been confirmed to have positive effects on the health, productive performance, immune response and egg quality of laying hens .…”
Section: Introductionmentioning
confidence: 99%